The Modulation Effect on the ELVEs and Sprite Halos by Concentric Gravity Waves Based on the Electromagnetic Pulse Coupled Model - Chao Wang; Ying Wen; Jinbo Zhang; Qilin Zhang; Juwei Qiu (Atmosphere, 2021)
By employing the finite-difference time-domain method, the processes of electric field variation and morphological development of the optical radiation field of ELVEs and sprite halos were simulated in this article. Simulations of ELVEs show two optical radiation field centers, with a concentrated luminous zone from 85 to 100 km and an inner weaker optical radiation center. The electric field exhibits an obvious sparse and dense ripple pattern induced by the concentric gravity waves (CGWs) at altitudes of 90–100 km, which mainly occurs during the decline period of electric field with a shallow steepness. The alternating distance of the variations in the sparse and dense patterns is about 40 km, which corresponds to the horizontal wavelength of the electric field. The CGWs induce significant deformation of the inner optical radiation field, even splitting into multiple luminous regions. Simulations of sprite halos indicate that the horizontal range of the electrical field generated by lightning current is within 50 km, and a strong local electric field formed in the region right above the lightning channel is due to the small-scale breakdown current. Thus, the increased electron density shields the upper regions and reduces the electrical field’s strength. The sprite halos luminous zone is pancake-shaped, and it originates at 85 km along with a downward developing trend. The disturbance of sprite halos’ luminescence caused by CGWs mainly occurs at about 80–100 km directly above the lightning channel, and the primary deformation zone is located within 30 km of the lightning channel, which is also the region with the most recognizable electric field disturbance.